Factors associated with recurrence and survival in livertransplant patients with HCC - a single center retrospective study (2015)
ABSTRACT: Introduction. Hepatocellular carcinoma is the most common primary tumor of the liver and is diagnosed in more than a half million people worldwide each year. This study aims to assess factors associated with the recurrence and survival of patients with hepatocellular carcinoma and liver transplantation in a cohort of patients from Medellín, Colombia. Material and methods. This was a descriptive retrospective study of a consecutive series of liver transplant patients from the Pablo Tobon Uribe Hospital of Medellín from January 2004 to May 2013. Demographic, clinical, imaging, and pathology variables were analyzed. Results. Three hundred thirty liver transplants were performed during the study period, 54 cases (16.4%) had one or more hepatocellular carcinomas in the explant, and 79.6% of these patients were men. Cirrhotic patients had different etiologies, but most of them were due to alcohol abuse (22.2%), followed by hepatitis B virus infection (20.4 %), and hepatitis C virus infection (18.5%). In the pathology specimen, 51.9% had only one focus of hepatocellular carcinoma, 22.2% had two foci and 12.9% had three tumors. Recurrence of hepatocellular carcinoma occurred in 7.4% patients with an average time of 81 months. During follow-up, 25.9% of the patients died in an average time of 67.9 months (CI95 59.1-80.1 months). Conclusion. Recurrence and survival of patients with liver transplantation for hepatocellular carcinoma in this study had a similar behavior as that reported in the world literature. The factors associated with these outcomes were vascular invasion, poor tumor differentiation and satellitosis.